2014
DOI: 10.1364/oe.22.007160
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Airy beams, nonlinear accelerating beams, and induced solitons in Kerr and saturable nonlinear media

Abstract: Abstract:We investigate numerically interactions between two in-phase or out-of-phase Airy beams and nonlinear accelerating beams in Kerr and saturable nonlinear media in one transverse dimension. We discuss different cases in which the beams with different intensities are launched into the medium, but accelerate in opposite directions. Since both the Airy beams and nonlinear accelerating beams possess infinite oscillating tails, we discuss interactions between truncated beams, with finite energies. During int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 34 publications
5
109
0
2
Order By: Relevance
“…Airy beams which are regarded as the zeroth-order Olver beams attract the attention of a lot of scientists of the laser community [24]- [30]. These zeroth-order Olver (Airy) beams have been the subject of many other studies in various optical systems, be it aligned, misaligned, turbulence, crystal, Kerr media [31]- [36] or others. More recently, Liu et al [37] have obtained an approximate analytical expression for the propagation of an Airy-Gaussian beams passing through an ABCD optical system with a rectangular annular aperture.…”
Section: Introductionmentioning
confidence: 99%
“…Airy beams which are regarded as the zeroth-order Olver beams attract the attention of a lot of scientists of the laser community [24]- [30]. These zeroth-order Olver (Airy) beams have been the subject of many other studies in various optical systems, be it aligned, misaligned, turbulence, crystal, Kerr media [31]- [36] or others. More recently, Liu et al [37] have obtained an approximate analytical expression for the propagation of an Airy-Gaussian beams passing through an ABCD optical system with a rectangular annular aperture.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been confirmed that Airy beams can exist in photonic lattices and give rise to interesting phenomena, such as accelerating lattice solitons [48]. And we have investigated the interactions of Airy beams in different NL media [29,30]. The governing nonlinear Schrödinger equation (NLSE) can now be written as…”
Section: Nonlinear Guidancementioning
confidence: 99%
“…In 2009, Ellenbogen et al produced an Airy beam in an asymmetrically modulated quadratic optical NL medium by the three-wave mixing process [25]. This novel nonlinear generation method not only produced an Airy beam at a new wavelength and a higher energy, but also provided new possibilities for manipulating the dynamics of Airy beams in NL media [26][27][28][29][30]. According to the nonlinear Schrödinger equation, the nonlinearity plays a nontrivial role in controlling the persistence as well as the breakdown of Airy beams [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…We are interested in an intensity regime where the effects of NLLs are significant, being comparable to, or even dominant over other nonlinear effects (Kerr nonlinearity in our case). This means in particular that the possible solitary structures emerging from the Airy beam due to the Kerr nonlinearity, as described in [10], are significantly affected by NLLs. This condition is fulfilled if the intensity n 0 /(k 2 0 n 2 x 2 0 ) required for soliton formation is higher than, or of the order of the typical intensity (2/β (M) kx 2 0 ) 1/(M−1) at which NLLs are significant.…”
Section: Dynamics Of Ideal Airy Beams In the Nonlinear Mediummentioning
confidence: 99%
“…It was indeed in Optics where the land was prepared thanks to the re-discovery in the eighties of non-diffracting Bessel beams [4]. Since then huge amount of work has been made on self-accelerating Airy beams, including their properties [5,6], propagation dynamics in different nonlinear media [7][8][9][10][11][12], nonparaxial [13], vectorial [14] and fully nonlinear [15] generalizations, and applications as diverse as particle clearing [16] or creation of curved plasma channels [17]. It seems that this amount of work was necessary to close the circle with the recent creation of genuine quantum Airy wave packets of free electrons [18].…”
Section: Introductionmentioning
confidence: 99%